Beyond Borders: Language Barriers for Accessing to Education for Rohingya Children in Bangladesh, Indonesia, and Malaysia (Mother Language, 2025)
This research aims to explore language barriers in accessing education for Rohingya children as refugees in Bangladesh, Indonesia, and Malaysia. As one of the most marginalized and displaced communities globally, Rohingya children face significant obstacles in realizing their right to education, exacerbated by linguistic differences in their host countries. By employing a comparative analysis framework, it attempts to elucidate the nuanced dynamics of language barriers and their impact on educational access and outcomes within diverse socio-political contexts. This study collected qualitative data from secondary sources and some by observation as primary data. It also used a document analysis method to examine the intersection of language, policy, and practice in educational settings catering to Rohingya children in the host countries after their arrival a few years ago. The paper discusses present language policies and practices in shaping the educational inclusion of the Rohingya children in overcoming the language-related barriers in those three countries. This study has made a comparison of the education and learning processes of the Rohingya children in Bangladesh, Indonesia, and Malaysia. It is observed that ensuring quality education for all refugee children is more difficult than basic education based on technical or non-formal only. However, the paper contributes to the broader arena of refugee education and their language rights.Mother Language 2024; 8(1-2): 5-26